#1**+1 **

Complete the square:

p^2 + 10 p = 1

Move everything to the left hand side.

Subtract 1 from both sides:

p^2 + 10 p - 1 = 0

Move the constant term to the right hand side.

Add 1 to both sides:

p^2 + 10 p = 1

Group terms together on the left hand side.

Group terms together on the left hand side, with a placeholder constant:

(p^2 + 10 p + __) = __ + 1

Find the appropriate term to place inside (p^2 + 10 p + __).

Take one half of the coefficient of p and square it, then add it to both sides.

Add (10/2)^2 = 25 to both sides:

(p^2 + 10 p + 25) = 25 + 1

(p^2 + 10 p + 25) = 26

Express p^2 + 10 p + 25 as a square.

p^2 + 10 p + 25 = (p + 5)^2:

**(p + 5)^2 = 26**

Guest Sep 5, 2019